Analisis Risiko Gangguan Otot Rangka pada Pekerja Pengelolahan Tembakau X di Jawa Timur - Rochmania, Aidina; Muna, Kuuni Ulfah Naila El; Khrisnawati, Utami; Rosyid, Muh Agus Ainur (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Skeletal muscle disorders are discomfort that arises due to injuries to muscles, tendons, joints, nerves, and soft tissues during work. This research method uses a cross-sectional study design. Data collection was conducted from January to July 2023 in the sector of tobacco processing in East Java. Workers in tobacco processing sector X, while performing their tasks using plastic chairs without proper ergonomic support, can lead to complaints of skeletal muscle disorders. The aim of this research is to analyze the risk of complaints of skeletal muscle disorders in the work of tobacco processing X. The sampling technique used random sampling with a sample size of 9 respondents. Measurement of skeletal muscle disorder complaints used a questionnaire based on SNI 9011:2021. Data analysis was done using the Chi-square test. The test results show that physical fatigue, job tasks, and age are related to complaints of skeletal muscle disorders. Efforts to reduce the risk of skeletal muscle disorders at workers in tobacco processing X in East Java are recommended to use ergonomic chairs, take breaks, and perform relaxation movements.